Automatic Door Control System Using SMS Gateway Base on Arduino Uno and Ultrasonic Sensor - Faroqi, Adam; Fitriadi, Adi; Utami Adiningsih, Neni; Ali Ramdhani, Muhammad (International Journal of Engineering and Technology, 2018)
The purpose of this research is to design an automatic door control system using media consist of Arduino Uno, SMS Gateway, ultrasonic sensor, relay, accu (batterai), buzzer, and adapter. The design methodology did with several stages: software design, hardware design, system implementation, and system testing. The design results show the system works well for opening and locking doors via SMS Gateway, as well as alerting via SMS when the door opened forcibly.Â Â